Zigbex wireless sensor actuator network (WSAN) home alarming system for air conditioning / Nor Fazlina Ismail - Ismail, Nor Fazlina (2011)
This project present the application of zigbex wireless sensor or actuator network (WSAN) home alarming system for air conditioning. The main aim of this project is to implement a WSAN for air conditioning system that based on temperature. Measurements level of temperature give information to consumer about air conditioning condition. The sensor node will sense the level of temperature and sends the data to the base node and actuator node. The results were display on the oscilloscope Graphical User Interface (GUI) whereas the actuator node would activate the alarm. This project applied the temperature/humidity sensor that could be used as main component or part for the system to operate. The sensor is controlled by zigbex and its program by NesC coding program. It can be concluded that air conditioning can be controlled wirelessly using zigbex WSAN test-bed.